The interaction of lipocalin-2 and astrocytes in neuroinflammation: mechanisms and therapeutic application - Tan, Qianqian; Zhang, Chenxi; Rao, Xiuqin; Wan, Wei; Lin, Wei; Huang, Shupeng; Ying, Jun; Lin, Yue; Hua, Fuzhou (Frontiers in Immunology, 2024)
Neuroinflammation is a common pathological process in various neurological disorders, including stroke, Alzheimer's disease, Parkinson's disease, and others. It involves the activation of glial cells, particularly astrocytes, and the release of inflammatory mediators. Lipocalin-2 (Lcn-2) is a secretory protein mainly secreted by activated astrocytes, which can affect neuroinflammation through various pathways. It can also act as a pro-inflammatory factor by modulating astrocyte activation and polarization through different signaling pathways, such as NF-κB, and JAK-STAT, amplifying the inflammatory response and aggravating neural injury. Consequently, Lcn-2 and astrocytes may be potential therapeutic targets for neuroinflammation and related diseases. This review summarizes the current knowledge on the role mechanisms, interactions, and therapeutic implications of Lcn-2 and astrocytes in neuroinflammation.